Contributions of positive psychology in the prevention of occupational risks - ZAIBET, Meriem (Journal of Human Sciences, 2022)
This article aims to determine the contributions of positive psychology to build a  healthy and serene work environment by applying the conditions of well-being in the workplace with the aim to reduce and prevent psychosocial risks. Positive psychology consists in reinforcing the virtues of individuals to achieve personal, social and organizational fulfillment. It affects all aspects of human life including the world of work. As a result, well-being at work has become the priority of all organizations. Many studies in organizational psychology have shown that in its absence – well-being at work – employees suffer serious consequences in addition to moral suffering and reduced performance.